A practical process mining approach for compliance management. Issue 4 (19th July 2019) - Becker, Michael; Buchkremer, Rüdiger
Abstract : Purpose: The purpose of this study is to examine whether the compliance management activities in the risk management environment of financial institutions can be enhanced using a Process Mining application. Design/methodology/approach: In this research, an implementation procedure for a selected Process Mining application is developed and evaluated at a financial institution in Germany. Findings: The evaluation of the process data with the Process Mining application Disco shows that the compliance of the real-life execution of business processes can be monitored in real-time. Moreover, potential non-compliant activities and durations can be analysed in a detailed manner. Research limitations/implications: When the research results are regarded, it must be considered that a general condition for the usage of a Process Mining application is that the process data is available and exportable in the required format and that data privacy regulations are fulfilled. Originality/value: This research presents a practical use case for the implementation of a Process Mining application at the risk management department of financial institutions. It shows the value of using a technical application to carry out tedious tasks that are usually executed manually. This value is discussed and compared with the aim to help financial institutions in determining how the effectiveness and efficiencies of compliance management activities can be improved. Therefore, this research can be taken as a foundation for the practical implementation of a Process Mining application at financial institutions.